Carrier-Based Modulation Scheme Plus Neutral-Point Current Control for Balancing Neutral-Point Voltage of Three-Phase Four-Leg Three-Level Inverter Over Entire Power Factor - Wang, Yuhao; Zhang, Li; Yin, Tianxiang; Lin, Lei; Shi, Xiaojie (Conference proceedings - IEEE Applied Power Electronics Conference and Exposition, 2024)
The carrier-based pulse-width-modulation (CB-PWM) plus neutral-point (NP) voltage control is a straightforward and efficient method for modulating the three-phase four-leg three-level (3P4L 3L) inverter. This paper reveals that, even with the implementation of the NP voltage control loop, the neutral-point (NP) voltage of the 3P4L 3L inverter becomes imbalanced at an output power factor (PF) of 0. The root cause is analyzed, indicating that the gain sign of the NP voltage control loop should not be constant, when the output voltages' phase is subject to different polarities of perturbations in the case of PF=0. To address this issue, a novel modulation scheme is proposed in this paper to regulate the gain sign of the NP voltage loop according to the NP current direction, for balancing the NP voltage over the entire power factor. Furthermore, the CB-PWM plus NP current control is proposed to substitute the CB-PWM plus NP voltage control. This approach not only balances the NP voltage but also reduces the NP voltage ripple across the entire power factor range. Finally, the simulation results are presented to verify the feasibility of the proposed scheme.